2020
DOI: 10.1177/2396987320954671
|View full text |Cite
|
Sign up to set email alerts
|

STudy of Antithrombotic Treatment after IntraCerebral Haemorrhage: Protocol for a randomised controlled trial

Abstract: Background and aims Many patients with prior intracerebral haemorrhage have indications for antithrombotic treatment with antiplatelet or anticoagulant drugs for prevention of ischaemic events, but it is uncertain whether such treatment is beneficial after intracerebral haemorrhage. STudy of Antithrombotic Treatment after IntraCerebral Haemorrhage will assess (i) the effects of long-term antithrombotic treatment on the risk of recurrent intracerebral haemorrhage and occlusive vascular events after intracerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“… 27 Several such randomized trials are ongoing. STATICH and RESTART‐France are currently investigating starting versus avoiding antiplatelet treatment after ICH, STATICH, 22 ENRICH‐AF, 34 ASPIRE, 35 PRESTIGE‐AF, 36 and A3ICH 37 are investigating starting versus avoiding anticoagulant treatment for atrial fibrillation after ICH. In addition, STROKECLOSE 38 is comparing left atrial appendage occlusion to the best medical treatment in ICH survivors with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Several such randomized trials are ongoing. STATICH and RESTART‐France are currently investigating starting versus avoiding antiplatelet treatment after ICH, STATICH, 22 ENRICH‐AF, 34 ASPIRE, 35 PRESTIGE‐AF, 36 and A3ICH 37 are investigating starting versus avoiding anticoagulant treatment for atrial fibrillation after ICH. In addition, STROKECLOSE 38 is comparing left atrial appendage occlusion to the best medical treatment in ICH survivors with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, we conducted two surveys, one in 2011 for antiplatelet treatment and one in 2015 for anticoagulant treatment. The three surveys were customized as preparation for randomized trials (STATICH in Scandinavia, RESTART and SoSTART in the United Kingdom), 13 , 15 , 22 which was the reason for the different approaches. The wording of the questions in the three surveys were different, but we were generally interested to measure the level of uncertainty among stroke physicians regarding this treatment dilemma.…”
Section: Methodsmentioning
confidence: 99%
“…In another small feasibility and safety trial (NASPAFICH, NCT02998905), patients with atrial fibrillation and intracerebral haemorrhage on or off anticoagulants were randomly allocated to a DOAC or aspirin; this study was stopped early after the inclusion of 30 patients. Five other studies are ongoing: ENRICH AF (NCT03950076), a study of edoxaban versus no anticoagulation in 1200 patients with intracranial haem orrhage and atrial fibrillation; ASPIRE (NCT03907046), which is assessing apixaban versus aspirin in 700 patients with intracerebral haemorrhage and atrial fibrillation; PRESTIGEAF (NCT03996772), assessing DOAC versus no antico agulation in 654 patients with intracerebral haemorrhage and atrial fibrillation; A3ICH (NCT03243175), assessing apixaban versus left atrial appendage occlusion versus no anticoagulation and no left atrial appendage occlusion in 300 patients with intracerebral haemorrhage and atrial fibrillation; and STATICH (NCT03186729), 29 assessing antithrombotic medication versus no antithrombotic medication in 500 patients with intracranial haemorrhage and an indication for antithrombotic drugs (including but not restricted to atrial fibrillation).…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials are currently investigating the optimal antithrombotic treatment strategy for stroke prevention in ICH survivors with concomitant AF, 9–14 and 2 of these trials have now been concluded and reported. 22,23 Both trials were inconclusive and likely underpowered to detect a signal of benefit or harm from OAC treatment, and the trial investigators call for additional trial data to provide more robust evidence.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Several randomized controlled trials are currently investigating antithrombotic treatment options for stroke prevention in ICH survivors with concomitant AF. [9][10][11][12][13][14] An ongoing European multinational randomized controlled trial, the PRESTIGE-AF (Prevention of Stroke in Intracerebral Haemorrhage Survivors With Atrial Fibrillation) trial is investigating stroke prevention strategies in patients with AF surviving an ICH. 13 Patients are randomized to either a nonvitamin K antagonist oral anticoagulant (NOAC) or no anticoagulation.…”
mentioning
confidence: 99%